The effect of perfusion on the flora of the excluded colon. Issue 3 (March 1973) - Vince, Angela; Bown, R.; O'Grady, F.; Dawson, A. M.
Abstract : The bacterial flora of excluded colonic segments of three patients has been examined in the normal resting state and following perfusion. The flora of the excluded colon was substantial and qualitatively similar to that of faeces. Perfusion for two hours at 10 ml per minute usually reduced counts of organisms present in the issuing effluent by 1 to 1½ logs in two patients, but rises in the counts of some organisms were recorded from the third patient. Prolonged rapid perfusion or the inclusion of antibiotics in the perfusing solution was necessary to obtain a substantial reduction in counts. Rapid perfusion resulted in the appearance of organisms that had not been recovered during slower perfusions.